Does the EU ETS cause carbon leakage in European manufacturing? - Helene Naegele; Aleksandar Zaklan (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Carbon leakage is an issue of major interest in both academic and policy debates about the effectiveness of unilateral climate policy addressing global externalities. The debate is particularly salient in Europe, where the EU Emissions TradingSystem (EU ETS) covers emissions of many traded sectors. In a first step, we review how carbon leakage and the pollution haven effect are defined and identified in the literature. In a second step, we evaluate whether the emission cost introduced by the EU ETS has caused carbon leakage in European manufacturing. We compute trade flows in embodied carbon and value, using GTAP trade and input-output data and administrative data from the EU ETS. We evaluate theeffect of four measures of environmental stringency on both net trade flows and bilateral trade flows. We do not find evidence that the EU ETS has caused carbon leakage.
Keywords: F18; Q58; Q54; 330; carbon leakage; pollution haven; EU ETS; cap-and-trade; CO2 emissions; policy evaluation